Role of some psychrotrophic aerobic sporeforming bacteria in spoilage of raw milk - عبد المنعم, معتز عبد الواحد; الخزرجي, نجم هادي; علي سلطان, عماد ابراهيم (The Iraqi Journal of Veterinary Medicine, 2004)
This study was planned to isolated and identify some psychrotrophic aerobic sporeforming bacteria from raw milk and determine the predomenant isolate. Microbiological estimations were performed for (100) raw milk samples collected from four sources (filters, stations, bulk tanks and milk containers) and for the same samples after heat treatment at 80°C for (12) minutes and upon subsequent storage at (7)°C for 0,7,14 and 21 days. The Aerobic plate count (APC) was determined and the total bacterial count were compared with each of the mesophilic sporeformer count (MSFC) at (0) & (7) days of storage & the psychrotrophic sporeformer count (PSFC) upon storage at (7)°C for 0,7,14 and 21 days. Positive relationship existed between the increase in (APC) before heat treatment & the increase in (MSFC) at (0) or (7) days or (PSFC) at 0,7,14 & 21 days of storage at 7°C. Immediately after heat treatment at (80)°C for 12 minutes 59% of the samples had psychrotrophic sporeformer counts of <10 cfu/ml, but after (21) days of storage at (7)°C, 79% of the samples had counts of > 109 cfu/ml. Bacillus cereus and Bacillus mycoides were identified as the predominant psychrotrophic sporeformers in the heated milk, stored at 7°C. The results confirmed that growth of heat-resistant psychrotrophicsporeforming organisms co-incide with spoilage of heated milk, and was a higher than of the normal pasteurization temperatures or longer time which enhanced the germination of these spores. psychrotrophic sporeformers have been shown to be responsible for such off-flavors (bitter, stale, rancid and putrid) of heated milk stored at (7)°C for (21) days, and sweet curdling observed in 70% of the samples in the forms of "buttons” at the bottom of the containers after (21) days of storage at (7)°C. Most of the isolated psychrotrophic B cercus were able to produce porteinase, lipases and lecithinase enzymes beside the haemolysin. It was concluded that the number of (PSFC) in raw milk conditions prevailing sanitary the depends upon apparently during production and upon time and temperature of milk storage before processing.